Asymptotic Behavior of Solutions of Singular Integro-differential Equations - Dauylbaev, M.K.; Mirzakulova, A.E. (Discontinuity, Nonlinearity, and Complexity, 2026)
We study the asymptotic behavior of the two-point integral boundary value problem for third order integro-differential equations with the small parameter at two highest derivatives. The asymptotic estimations of the solution of the integral boundary value problem is obtained. The obtained results shown that the solution of integral boundary value problem on both sides of given segment has the initial jumps with different orders.